A highly stabilized Ni-rich NCA cathode for high-energy lithium-ion batteries. (June 2020) - Ryu, Hoon-Hee; Park, Nam-Yung; Seo, Jeong Hyun; Yu, Young-Sang; Sharma, Monika; Mücke, Robert; Kaghazchi, Payam; Yoon, Chong S.; Sun, Yang-Kook
Graphical abstract: Abstract: In this study, we have demonstrated that boron doping of Ni-rich Li[Ni x Co y Al1− x − y ]O2 dramatically alters the microstructure of the material. Li[Ni0.885 Co0.1 Al0.015 ]O2 is composed of large equiaxed primary particles, whereas a boron-doped Li[Ni0.878 Co0.097 Al0.015 B0.01 ]O2 cathode consists of elongated particles that are highly oriented to produce a strong, crystallographic texture. Boron reduces the surface energy of the (0 0 3) planes, resulting in a preferential growth mode that maximizes the (0 0 3) facet. This microstructure modification greatly improves the cycling stability; the Li[Ni0.878 Co0.097 Al0.015 B0.01 ]O2 cathode maintains a remarkable 83% of the initial capacity after 1000 cycles even when it is cycled at 100% depth of discharge. By contrast, the Li[Ni0.885 Co0.1 Al0.015 ]O2 cathode retains only 49% of its initial capacity. The superior cycling stability clearly indicates the importance of the particle microstructure (i.e., particle size, particle shape, and crystallographic orientation) in mitigating the abrupt internal strain caused by phase transitions in the deeply charged state, which occurs in all Ni-rich layered cathodes. Microstructure engineering by surface energy modification, when combined with protective coatings and composition modification, may provide a long-sought method of harnessing the high capacity of Ni-rich layered cathodes without sacrificing the cycling stability.